PK/PD Study of Mycophenolate Mofetil in Children With Systemic Lupus Erythematosus to Inform Model-Based Precision Dosing - Yewei Chen; Li Sun; Hong Xu; Min Dong; Min Dong; Tomoyuki Mizuno; Tomoyuki Mizuno; Alexander A. Vinks; Alexander A. Vinks; Hermine I. Brunner; Hermine I. Brunner; Yifan Li; et al. (Frontiers Media S.A., 2020)
Objectives: To evaluate the mycophenolic acid [MPA, the active form of mycophenolate mofetil (MMF)] pharmacokinetic parameters in relation to clinical response to identify target exposure ranges in pediatric patients with systemic lupus erythematosus (SLE).Methods: This was a retrospective study using pharmacokinetic data collected in 67 pediatric patients aged 4-18 years with SLE. Target MPA exposures for effective inhibition of SLE activity (as measured by SLE disease Activity Index (SLEDAI), active SLE was defined as a SLEDAI score of ≥6, and a controlled disease was defined as a SLEDAI score of ≤4) were assessed by receiver operating characteristic (ROC) curve and logistic regression. Exposure-response models were developed to quantitatively describe the relationship between SLEDAI score and AUC0-12 or Ctrough, respectively.Results: The MPA AUC0-12 in patients with active SLE was significantly lower than that in patients with inactive SLE. ROC analysis revealed that an AUC0-12 threshold of 39 μg h/ml or a Ctrough of 1.01 μg/ml was associated with the lowest risk of active SLE. Logistic regression analysis revealed that an AUC0-12 of less than 34 μg h/ml or a Ctrough of less than 1.2 μg/ml probably is associated with active SLE. The results of the exposure-response modeling also indicated that an AUC0-12 less than 32 μg h/ml or a Ctrough less than 1.1 μg/ml was associated with suboptimal clinical outcome. An AUC0-12 above 50 μg h/ml or a Ctrough above 1.7 ug/ml was associated with disease control.Conclusion: Both AUC0-12 and Ctrough of MPA are predictive of the likelihood of active SLE in pediatric patients receiving MMF. An individualized dosing regimen of MMF, with a target AUC0-12 or Ctrough, should be considered for SLE patients.